2020
DOI: 10.1021/acsami.9b20801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trapped Solvent on the Interface between PS-b-PMMA Thin Films and P(S-r-MMA) Brush Layers

Abstract: The orientation of block copolymer (BCP) features in thin films can be obtained by spin-coating a BCP solution on a substrate surface functionalized by a polymer brush layer of the appropriate random copolymer (RCP). Although this approach is well established, little work reporting the amount and distribution of residual solvent in the polymer film after the spin-coating process is available. Moreover, no information can be found on the effect of trapped solvent on the interface between the BCP film and RCP br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…In this case, the chemical pattern created guides the perpendicular-oriented lamellae, achieving the DSA. As previously reported in the literature, experimental [24,25] and computational [26] studies confirmed that the interpenetration region between systems consisting of polymeric films deposited onto grafted brush layers increases with the molar mass of the brush layer by fixing the molar mass of the polymer film. Although these previous studies investigated the interpenetration between layers and not the lateral interpenetration, they can be useful to give a plausible explanation to the results obtained in the present work.…”
Section: Discussionsupporting
confidence: 85%
“…In this case, the chemical pattern created guides the perpendicular-oriented lamellae, achieving the DSA. As previously reported in the literature, experimental [24,25] and computational [26] studies confirmed that the interpenetration region between systems consisting of polymeric films deposited onto grafted brush layers increases with the molar mass of the brush layer by fixing the molar mass of the polymer film. Although these previous studies investigated the interpenetration between layers and not the lateral interpenetration, they can be useful to give a plausible explanation to the results obtained in the present work.…”
Section: Discussionsupporting
confidence: 85%
“…In previous work we demonstrated that the presence of residual toluene in spin‐coated PS‐ b ‐PMMA thin films significantly affects the SA and grain coarsening processes 21–23 . This residual solvent is located at the interface between the random brush layer that is used to neutralize the substrate and the block copolymer thin film and represents a reservoir of solvent that is progressively released during the annealing process.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group demonstrated that by properly increasing the heating rate at 18 °C s −1 in a rapid thermal processing (RTP) machine, the onset of the degradation process of PDMS‐containing DBC thin films shifts to T > 400 °C, permitting operation at T = 310 °C without any evidence of degradation 20 . Moreover, we demonstrated that the solvent that is naturally trapped in the polymeric film during the spin coating process significantly influences the correlation length ( ξ ) evolution in PS‐ b ‐PMMA (PMMA, polymethylmethacrylate) DBC films during a thermal treatment performed in the RTP machine 21–23 . In particular, we showed that, after a ramp to achieve the target temperature of the thermal treatment, there is still a considerable amount of residual solvent retained in the block copolymer films that increases the polymer chain diffusivity and accelerates the kinetics of the SA process 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Relaxing the assumption of uniform brush thickness and introducing selective affinity of the substrate or the top in a model can produce a more enriched phase behavior. The morphologies of BCP brushes under solvents have also been studied using SCFT [26][27][28][29][30] , lattice Monte Carlo 31,32 , single-chain-in-mean-field (SCMF) 33 , dissipative particle dynamics (DPD) 34,35 , hybrid Molecular Dynamics(MD) with field representation of non-bonded interactions 36,37 ,and density functional theory (DFT) simulations 38 . Despite such explorations, obtaining a comprehensive understanding on the formation of morphology in brush systems under different conditions, i.e., melt or exposed to solvent molecules, has been a key challenge.…”
Section: Introductionmentioning
confidence: 99%